Effects of benzoic acid, essential oils and Enterococcus faecium SF68 on growth performance, nutrient digestibility, blood profiles, faecal microbiota and faecal noxious gas emission in weanling pigs. Issue 1 (1st January 2016) - Zhang, Z.F.; Rolando, A.V.; Kim, I.H.
Abstract : A total of 150 weanling pigs (body weight of 8.86 ± 0.93 kg) were used in a 42-day trial to evaluate the efficacy of benzoic acid (BA), essential oils (EO) and Enterococcus faecium SF68. Pigs were randomly distributed into five treatments (six replicates and five pigs per pen): CON, control diet; B5E, CON + 0.5% BA + 0.01% EO; B5SF, CON + 0.5% BA + 7 × 10 8 CFU/kg E. faecium ; B3E, CON + 0.3% BA + 0.01% EO; B3SF, CON + 0.3% BA + 7 × 10 8 CFU/kg E. faecium . During d 8–21 and overall, pigs fed B5E diets showed greater ( P < 0.05) average daily gain and gain/feed ratio than CON. The dry matter digestibility in pigs fed B5E diet was increased ( P < 0.05) compared with CON at d 21, while the nitrogen digestibility in B5E, B5SF and B3E was increased ( P < 0.01) compared with CON. Faecal Lactobacillus counts were increased in B5E, whereas E. coli counts were decreased in B5E and B5SF ( P < 0.01) compared with CON. All the supplementation treatments decreased ( P < 0.05) the faecal NH3, total mercaptans and H2 S emission. In conclusion, dietary inclusion of 0.5% BA plus 0.01% EO and 7 × 10 8 CFU E. faecium /kg of diet could improve growth performance, decrease faecal E. coli counts, while 0.3% BA combination with EO or E. faecium almost had no effect on the parameters except the decreased faecal noxious gas contents.